Book review: Listening to Young Children: a Guide to Understanding and Using the Mosaic Approach. London: Jessica Kingsley ISBN: 9781909391260 - Alison Clark (Scottish Journal of Residential Child Care)
This is the third edition of a highly regarded text in research methods with young children. It combines work covered in previous books by the author into one expanded, yet accessible book that will be particularly useful for anyone interested in involving young children in their research.